MAPPING CUSTOMARY SPATIAL STRUCTURE FOR SPATIAL PLANNING INTEGRATION IN THE MERATUS GEOPARK - MUHAMMAD MALIKI (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
Geopark management increasingly requires approaches that connect landscape conservation with the spatial systems embedded in local communities. In the Meratus Geopark, this issue is particularly important because several customary territories have recently obtained formal legal recognition, while their spatial structures remain only weakly translated into formal spatial planning frameworks. This study aims to identify and map the customary spatial structure of four formally recognized customary law communities in Loksado District and to assess its relevance as an initial basis for spatial integration in the Meratus Geopark. The research adopts a qualitative comparative case study design, grounded in document analysis and spatial interpretation. Data were drawn from four decrees of the Regent of Hulu Sungai Selatan and their appendices, which contain profiles of customary territories, customary spatial categories, land tenure and access arrangements, customary institutions, and customary maps. The analysis combined structured data extraction, qualitative content analysis, cross-case comparison, and the translation of customary spatial categories into planning-relevant spatial functions. The results show that the four customary territories contain internally differentiated spatial categories that consistently correspond to protective, productive, transitional, settlement, and sacred functions, and in some cases to water-related functions. The study contributes an analytical bridge between the formal recognition of customary territories and more context-sensitive spatial integration in the Meratus Geopark